2021
DOI: 10.3390/su132313431
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and Conflict Management in the University Environment. Analysis of Students of the Degrees in Labour Relations and Human Resources, and Social Work at the University of Granada (Spain)

Abstract: In 2015 the United Nations approved the 2030 Agenda which established 17 Sustainable Development Goals (SDGs). The importance of these SGDs to universities, and universities’ commitment to them, requires not only involvement but also the development of research projects, instruments and practices that enable the SDGs to be carried out. Conflict is inherent within any social group and the need to perceive, analyse and manage it is crucial in order to move towards sustainable social development. This research pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Diversos estudios señalan la necesidad y desarrollo de programas de prevención y gestión positiva de conflictos, incluyendo la mediación y la educación para la convivencia en las instituciones universitarias (García-Villaluenga, 2009;Rommel y Bailey, 2016;Martínez-Martín y Lozano-Martín, 2021). Sin embargo, su valoración e implementación aún es muy residual.…”
Section: La Gestión De Conflictos En La Universidadunclassified
“…Diversos estudios señalan la necesidad y desarrollo de programas de prevención y gestión positiva de conflictos, incluyendo la mediación y la educación para la convivencia en las instituciones universitarias (García-Villaluenga, 2009;Rommel y Bailey, 2016;Martínez-Martín y Lozano-Martín, 2021). Sin embargo, su valoración e implementación aún es muy residual.…”
Section: La Gestión De Conflictos En La Universidadunclassified
“…Previous research mainly focused on teacher-student relationship conflict [17,18] but seldomly mentioned other types of teacher-student conflict. Several studies consistently concluded that relationship conflict is not conducive to students' creativity [18,19].…”
Section: Conflict Theory and Creativitymentioning
confidence: 99%
“…Conflict is the disagreement in opinions between people or groups [14][15][16]. The occurrence of conflict in the classroom is uncontrollable and unpredictable [17]. Previous research emphasized encouraging students' competence to solve uncertainty for enhancing students' creativity.…”
Section: Introductionmentioning
confidence: 99%
“…Universities have a responsibility to transform knowledge to create an impact in society. Higher education is a place for learning, research and innovation (Martínez-Martín & Lozano-Martín, 2021). Within the organization the quality and capabilities of human resource management talents directly affect the efficiency of organization's talent utilizations.…”
Section: Introductionmentioning
confidence: 99%